Analisis Potensi dan Pengembangan Kerbau Lumpur di Kabupaten Serang - Komariah, Komariah; Burhanuddin, Burhanuddin; Permatasari, N. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
Serang District is one of swamp buffalo sentra in Banten Province. The aim of study analyzed Additional Capacity of Ruminant Population (ACRP) and swamp buffalo’s productivity in Serang Regency. The number of observation were 64 buffaloes. The result of Additional Capacity of Ruminant Population (ACRP) analysis showed that the population of ruminant livestock in Serang District exceeds the capacity of ruminants based on forage potential of -10 529.68 AU. The cows and bull swamp buffalo productivity hip width was very significant difference (P<0.01). The swamp buffalo is very potential to be developed in Serang District and has high productivity.